Obesity Cut-Off Points Using Prepregnancy Body Mass Index according to Cardiometabolic Conditions in Pregnancy - Renata O. Neves; Alexandre da S. Rocha; Bruna O. de Vargas; Daniela C. Kretzer; Salete de Matos; Marcelo Z. Goldani; Lisia von Diemen; José A. de A. Magalhães; Juliana R. Bernardi (Journal of Pregnancy)
Aim. To suggest cut-off points for body mass index (BMI) using gestational hypertension, preeclampsia, and gestational diabetes mellitus (GDM) as cardiometabolic conditions in pregnancy. Methods. In this prospective study, singleton pregnant women from the fetal medicine service of the Brazilian Unified Health System were included. The pregnancy, perinatal, and newborn data were obtained from the clinical medical records. Maternal anthropometry included an assessment of weight and height and the prepregnancy BMI evaluation categorized according to the World Health Organization cut-off points. The area under the curve and confidence interval values from receiver operator curves were generated to identify the optimal cut-off points using prepregnancy BMI with better sensitivity and specificity. Results. Data on 218 pregnancies were analyzed, with 57.9% (n=124) being classified as overweight/obese, 11% (n=24) with GDM, 6.9% (n=15) with preeclampsia, and 11.0% (n=24) with gestational hypertension. The BMI cut-off points for predicting cardiometabolic conditions were 27.52 kg/m2 (S: 66.7%; E: 63.8%) for women with GDM; 27.40 kg/m2 (S: 73.3%; E: 62.4%; S: 79.2%; E: 64.9%; S: 70.3%; E: 66.3%) for women with preeclampsia, gestational hypertension, and gestational hypertension plus preeclampsia, respectively; and 27.96 kg/m2 (S: 69.6%; E: 65.6%) for women with preeclampsia plus GDM. Conclusion. The findings suggest that the optimal prepregnancy BMI cut-off point is around 27 kg/m2 for pregnant women with maternal cardiometabolic conditions.